Applying Asset-Based Community Development in Islamic Community Development for Disaster Resilience: An Integrative Review from an Indonesian Perspective - Ismiatul Ramadhian Nur; Rasyidah Rasyidah; Walid Amri; Risma Sunarty (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2026)
Disaster risk reduction (DRR) paradigms have progressively shifted from needs-based interventions toward asset-based approaches (ABA) that foreground community strengths, resources, and existing capacities. Following Whittemore and Knafl's (2005) five-stage framework (problem identification, literature search, data evaluation, data analysis, and presentation), this integrative review examines how ABA and Asset-Based Community Development (ABCD) intersect with community resilience and DRR, arguing that ABCD provides the operational and methodological framework for mapping and mobilizing local assets, while Pengembangan Masyarakat Islam (PMI, Islamic community development) provides the epistemological, ethical, and sociological paradigm that directs the purpose, values, and institutional grounding of that process in Muslim-majority settings such as Indonesia. Candidate studies were identified through Google Scholar and national journal databases (Garuda, SINTA), restricted to empirical research conducted in Indonesia and published in SINTA-accredited national journals (search period January-July 2026); every study considered for inclusion was individually verified against its original publication record (author, year, journal, and DOI/publisher link) before synthesis. Fourteen empirical studies, all situated in Indonesia and published between 2020 and 2026, met the inclusion criteria and were retained for methodological quality appraisal using the Mixed Methods Appraisal Tool (MMAT) and analyzed thematically through an inductive open-axial-selective coding process. Three themes were identified, each corresponding directly to one research sub-question: (1) the conceptualization and mobilization of local assets, (2) the role of Islamic institutional assets and social capital, and (3) the synthesis of findings through the Pengembangan Masyarakat Islam (PMI) paradigm. Findings suggest that mosques, majelis taklim, zakat and sharia-finance institutions, and local religious leaders recurrently function as pre-existing nodes of social capital that can be mobilized across the disaster cycle, complementing the broader shift from deficit-oriented to strength-oriented DRR practice. Because the corpus is limited to fourteen studies concentrated within Indonesia and skewed toward Java and Sumatra, findings should be read as indicative patterns specific to the Indonesian Muslim-majority context rather than cross-nationally generalizable conclusions. This review offers a conceptual foundation for further, more comprehensive empirical inquiry into faith-sensitive, community-led resilience programming in Indonesia, situated at the intersection of Asset-Based Community Development and Pengembangan Masyarakat Islam (Islamic community development).